Exploring the link between sedentary behavior and cognitive decline: a comprehensive study combining Mendelian randomization and animal model experiments - Bai, Yupeng; Liu, Mengke; Fang, Yan; Zhan, Ruonan (Frontiers in Psychology, 2024)
The causal link between detrimental behaviors and cognitive performance remains unclear. This research seeks to investigate the causal impact of adjustable lifestyle factors-namely, frequency of alcohol intake, onset of smoking, and sedentary activities like prolonged television viewing-on cognitive deterioration.This research combines large-scale genetic data from univariable and multivariable mendelian randomization analyses with experimental findings from animal models.Results: Our findings reveal that the odds ratio (OR) for cognitive function deterioration was 0.445 (IVW 95% CI: 0.370 to 0.536, p < 0.001) for each standard deviation increase in television watching time. After adjusting for body mass index (BMI), number of days walked /moderate activity over 10+ minutes and education in Multivariable Mendelian Randomization (MVMR), only the genetic predisposition to increased television watching time remained significantly associated with worse cognitive function (OR 0.659, 95% CI: 0.452 to 0.960, p = 0.030). The effects of the other two habits were not significant.Sensitivity analyses confirmed that genetic pleiotropy did not bias the results. To further explore the relationship between sedentary behavior and cognitive function, as well as the underlying mechanisms, we conducted a restricted cage housing experiment and a physical exercise training experiment in mice. The results showed that physical exercise significantly improved spatial memory, as assessed by the Morris water maze, and increased exploratory interest, as evaluated by the open field test and elevated plus-maze test, compared to the sedentary control group. These cognitive benefits may be mediated by mechanisms involving free radical scavenging and enhanced synaptic plasticity.Our research presents genetic evidence indicating that extended television viewing is linked to an elevated risk of cognitive decline. Additionally, experimental data from mouse models indicate that physical exercise can counteract cognitive decline and anxiety-like behaviors induced by sedentary behavior. This protective effect is likely mediated through ROS-dependent mechanisms that enhance synaptic plasticity in the hippocampus.